HUBUNGAN KOORDINASI MATA-TANGAN DAN KELENTUKAN PERGELANGAN TANGAN TERHADAP AKURASI SERVIS PENDEK BULUTANGKIS DI PB. ARHAM - Satari, Ahmad; Taheri Akbar, M.; Arvan Junaidi, Ilham (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low accuracy of short serves among badminton athletes at PB. Arham. The purpose of this study was to determine the relationship between hand-eye coordination and wrist flexibility with the accuracy of badminton short serves. This research employed a quantitative method with a correlational approach. The sample consisted of 15 PB. Arham athletes aged 14–17 years, selected using the total sampling technique. Data were collected through a hand-eye coordination test, a wrist flexibility test, and a badminton short-serve accuracy test. Data were analyzed using Product Moment correlation and multiple correlation techniques. The results showed a significant relationship between hand-eye coordination and short-serve accuracy (r = 0.882), as well as between wrist flexibility and short-serve accuracy (r = 0.757). Simultaneously, hand-eye coordination and wrist flexibility demonstrated a very strong relationship with short-serve accuracy (R = 0.892). It can be concluded that better hand-eye coordination and wrist flexibility contribute to higher short-serve accuracy among badminton athletes.